Knowledge support in learning operative organisations - Kasvi, Jyrki J. J. (Dissertations series / Helsinki University of Technology, Industrial Management and Work and Organizational Psychology, ISSN 1459-1936, 2003)
Summary (s. v).
Keywords: tietoyhteiskunta; organisaatio; oppiminen; osaaminen; kansanedustajat; tietotekniikka; koulutus : tietoyhteiskunta